A 2D Conductive Organic–Inorganic Hybrid with Extraordinary Volumetric Capacitance at Minimal Swelling. Issue 26 (16th May 2018) - Xiao, Kefeng; Jiang, Donglin; Amal, Rose; Wang, Da‐Wei
Abstract: Rational design and synthesis of 2D organic–inorganic hybrid materials is important for transformative technological advances for energy storage. Here, a 2D conductive hybrid lamella and its intercalation properties for thin‐film supercapacitors are reported. The 2D organic–inorganic hybrid lamella comprises periodically stacked 2D nanosheets with 11.81 Å basal spacing, and is electronically conductive (605 S m −1 ). In contrast to the pre‐existing organic‐based 2D materials, this material has extremely low gas‐permeable porosity (16.5 m 2 g −1 ) in contrast to the high ionic accessibility. All these structural features collectively contribute to the high capacitances up to 732 F cm −3, combined with small structural swelling at as low as 4.8% and good stability. At a discharge time of 6 s, the thin‐film intercalation electrode delivers an energy density of 24 mWh cm −3, which universally outperforms the surface‐dominant capacitive processes in porous carbons. Abstract : A layer‐structured organic–inorganic hybrid material with large lamellar period (11.81 Å), and good electrical conductivity (605 S m −1 ) is facilely self‐assembled into thin films on various conductive or insulating, and hydrophobic or hydrophilic, surfaces (metals, plastic, carbon, and glass), showing extraordinary volumetric capacitance up to 732 F cm −3 in aqueous salt solutions, with only 4.8–10.3% interlayer expansion.